(3JaSjQ GdbQBfs - (3YHO GdQRGb Hf geGe Hf fGaY GdMejQj, ehdGge, CHh HcQ GdUfYGfj,J (B211 (3g` s; (3eQJVj GdRHjOj , eMeO Hf eMeO Hf eMeO Hf YHO GdQRGb GdMSjfj, CHh GdajV,J (B1205 (3g` s
(3BNQgG (B:s
(3GfJgi GdLRA GdChd ef JaSjQ GdUfYGfi s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B70 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B282s
Keywords: (3GdJaSjQ hYdhe GdbQBfs